Bioremediation of Waste Water Containing Hazardous Cadmium Ion with Ion Imprinted Interpenetrating Polymer Networks. (16th April 2014) - Parameswaran, Girija; Mathew, Beena
Abstract : A novel Cd(II) ion imprinted interpenetrating polymer network (Cd(II)IIP) was prepared by free radical polymerization using alginic acid and NNMBA-crosslinked polyacrylamide in presence of initiator potassium persulphate. Cd(II)IIP showed higher capacity and selectivity than the nonimprinted polymer (NIP). The sorption capacities of Cd(II)IIP and NIP for Cd(II) ions were 0.886 and 0.663meqmole - 1, respectively. Kinetics studies showed that the sorption process closely agreed with a pseudosecond-order model. The thermodynamic data suggest that the sorption is a spontaneous endothermic process. Equilibrium experiments showed very good fit with the Langmuir isotherm equation for the monolayer sorption process. Cd(II)IIP exhibited good reusability, and the sorption capacity of Cd(II)IIP was stable within the first 4 cycles without obvious decrease. Also Cd(II)IIP showed almost 100% removal efficiency for Cd(II) ions in real environmental water samples, indicating that Cd(II)IIP could have wide application prospects in Cd(II) ion removal.